A previously undescribed coronavirus associated with respiratory disease in humans - Fouchier, Ron A. M. (National Academy of Sciences, 2004)
The etiology of acute respiratory tract illnesses is sometimes unclear due to limitations of diagnostic tests or the existence of as-yet-unidentified pathogens. Here we describe the identification and characterization of a not previously recognized coronavirus obtained from an 8-mo-old boy suffering from pneumonia. This coronavirus replicated efficiently in tertiary monkey kidney cells and Vero cells, in contrast to human coronaviruses (HCoV) 229E and OC43. The entire cDNA genome sequence of the previously undescribed coronavirus was determined, revealing that it is most closely related to porcine epidemic diarrhea virus and HCoV 229E. The maximum amino acid sequence identity between ORFs of the newly discovered coronavirus and related group 1 coronaviruses ranged from 43% to 67%. Real-time RT-PCR assays were designed to test for the prevalence of the previously undescribed coronavirus in humans. Using these tests, the virus was detected in four of 139 individuals (3%) who were suffering from respiratory illness with unknown etiology. All four patients suffered from fever, runny nose, and dry cough, and all four had underlying or additional morbidity. Our data will enable the development of diagnostic tests to study the prevalence and clinical impact of this virus in humans in more detail. Moreover, it will be important to discriminate this previously undescribed coronavirus from HCoV 229E and OC43 and the severe acute respiratory syndrome coronavirus.